HRM practices and performance of family-run workplaces: Evidence from the 2004 WERS - W. Stanley Siebert; Fei Peng; Yasheng Maimaiti (Institute for the Study of Labor (IZA), 2011)
This paper analyses HRM practices of family-run workplaces using the 2004 WERS. Family-ownership and management within workplaces in the corporate sector is our focus. This family-run group represents nationally about 26% of workplaces and 14% of employment. We find that employees in this group have stronger feelings of job security and loyalty, which we relate to family companies' HRM practices such as stronger support for long-term employment - an inclusivity linked to long-term orientation. We also find that family-owned and managed workplaces have better financial and quality performance measures than non-family, to which family-related HRM practices contribute.
urn:nbn:de:101:1-201108152066
Keywords: J01; L26; M54; 330; HRM practices; family business; loyalty; job security; financial performance